Drinking Water Quality Monitoring System - K.Tamilvaenthan, Bharani Tharan; Norfaiza Fuad (Evolution in Electrical and Electronic Engineering, 2024)
This study addresses the critical issue of drinking water contamination considering globalization and industrial development, emphasizing the paramount importance of ensuring safe water for public health and safety. Leveraging Internet of Things (IoT) technology, the paper explores the potential of IoT-enabled tools to detect and monitor contaminants in real-time, highlighting the need for innovative monitoring equipment capable of accurately measuring various water quality parameters. The urgency for affordable, portable, and precise monitoring tools capable of swiftly identifying a multitude of contaminants is underscored, along with the importance of standardized protocols and data formats for seamless integration with data analysis tools and IoT platforms. Addressing these challenges is essential to ensuring the provision of safe drinking water and mitigating the risk of waterborne illnesses globally. Additionally, the study provides a comprehensive analysis of water quality across various brands, focusing on pH, Total Dissolved Solids (TDS), Electrical Conductivity (EC), and temperature. The observed pH values fall within a narrow range, indicating neutral to slightly alkaline properties, meeting drinking water standards. TDS and EC values exhibit a broad spectrum, reflecting diverse mineral content, with lower values in brands sourced from treated tap water and higher values in natural mineral waters. Consistent water temperatures suggest controlled testing conditions. This data-rich analysis equips consumers with valuable insights to make informed choices based on preferences and health considerations.